2009
DOI: 10.1007/s12630-009-9200-0
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Neurological deficit associated with intraneural needle placement without injection

Abstract: Purpose Recent reports of painless intraneural injection of low volumes of local anesthetic without subsequent neurological deficit have led to the suggestion that deliberate subepineural injection may be a safe and therefore acceptable practice. Clinical features This report describes a case where a venous cannulation needle inadvertently penetrated a patient's median nerve. Sudden onset severe lancinating pain occurred in the median nerve sensory distribution. A subsequent thorough ultrasound examination sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[12] A functional consequence of intraneural injection of local anesthetic was described in one. [13] In a previous study on gel-nerve contact, we have reported limping as well as a consequence of nerve trauma. [14] Histologic changes of the spinal cord following intrathecal injection in the form of axonal degeneration was observed in an experiment on rats treated with greater than 16% prilocaine or mepivacaine or with greater than 4% bupivacaine.…”
Section: Resultsmentioning
confidence: 99%
“…[12] A functional consequence of intraneural injection of local anesthetic was described in one. [13] In a previous study on gel-nerve contact, we have reported limping as well as a consequence of nerve trauma. [14] Histologic changes of the spinal cord following intrathecal injection in the form of axonal degeneration was observed in an experiment on rats treated with greater than 16% prilocaine or mepivacaine or with greater than 4% bupivacaine.…”
Section: Resultsmentioning
confidence: 99%
“…19 However, there is some conflicting information on the role of mere puncture of the fascicles. [20][21][22] A variety of cellular changes accompany needle trauma, including alterations in membrane channel expression, activation of signal transduction, neuropeptide production, and an overall increase in excitability at the dorsal horn. 13 However, nerve puncture with intravenous cannulae or electroneurography needles have been shown to result in lasting neurologic deficit.…”
Section: Needle Traumamentioning
confidence: 99%
“…A complication of peripheral nerve blocks is the occurrence of iatrogenic nerve damage, but the incidence of long-term neurologic injuries is relatively low (3)(4)(5)(6). US-guided techniques for regional anesthesia have shown that peripheral nerves injected with local anesthetic do not inevitably suffer permanent neurological injuries (7)(8)(9)(10)(11)(12)(13)(14)(15), and some authors, contrary to other reports (16)(17)(18)(19), have challenged the risk of intraneural injections (7).…”
Section: Introductionmentioning
confidence: 99%